Intratextuality in Luke: Connecting the Emmaus Road with the Boy in the Temple. (November 2020) - James, Rob
The story of the boy Jesus in the Temple (Luke 2:41–51) and of the Road to Emmaus (Luke 24:13–35) are compared and are shown to be likely to be a deliberate piece of intratextuality on the part of the author of the Gospel of Luke. Four main agreements between the stories are examined. A motive for the intratextuality is also proposed in that it fits in very well with Luke's overall theological approach to the poor and the powerless.